Potential assessment of renewable energy resources and their power plant capacities in Iran - Mehrzad Khazaee; Rahim Zahedi; Reza Faryadras; Abolfazl Ahmadi (Global Journal of Ecology - Peertechz Publications, 2022)
Today, most developed and developing countries utilize renewable energy to meet their needs. The use of renewable energy prevents environmental pollution. A concern of the governments is to deal with environmental pollution. Iran as a major oil-producing country has increasingly paid attention to non-fossil energy resources, in particular renewable energy sources for its longer-term energy plans. In this paper, the types of renewable energy used in electricity generation in Iran have been studied. Studies show that during the last 20 years, 1.5% of the amount of electricity produced in Iran is supplied by renewable energy. Iran also has a much greater potential for utilizing renewable energy. By 2020, Iran has a potential of 42000 MW use of renewable energies. However, the capacity of renewable power stations constructed in Iran is 800 MW. Different regions of Iran have high wind, solar and geothermal energy potential, which has not been used enough to meet electricity needs.